Fabrication and characterization of nanostructured optical interconnect devices - Subodh Mhaisalkar. (2009)
Optical communication is one of the most important areas of research in the field of micro & opto-electronics, owing to the ever-increasing demand for bandwidth to enable a future with high-speed voice, video, and data system for homebuyers. Cost effective solutions and reliability of the optical modules pose significant challenges for the adoption of the optical technology on local area network. One of the major areas that the project focused on was the use of polymer based technologies for packaging of optical transceiver assemblies and to integrate polymeric waveguides and plasmonic resonance based devices into these devices. The project successfully determined the materials needed and the methodologies needed to maximise optical efficiency losses in these optical subassemblies. Novel methodologies to characterise time, temperature, and environment (humidity) based optical properties and to incorporate them into appropriate models were also developed.